Governing the ungovernable: practices and circumstances of governance in the irrigation sector - Venot, Jean-Philippe; Suhardiman, Diana (2014)
Since the early 2000s, governance has been at the core of the international water agenda. This has elicited calls for reforms in the irrigation sector, including efforts to address the problem of corruption. Nevertheless, the history of policy reform in the irrigation sector is one of repeated institutional refinements, which have hardly materialized into grounded policy measures and practices. Though international donors, policy makers, irrigation scholars and practitioners have long agreed to invest in the ‘soft issues’ of irrigation, most policy interventions have retained a focus on infrastructure-oriented development. This paper identifies decisive factors that preserve the status quo in irrigation development. We draw our analysis on empirical data from countries with a recent (Ghana, West Africa) and long (Indonesia) irrigation history. Beyond the idiosyncrasies of the two case studies that highlight that everyday practices are embedded in, and constrained by, existing institutional rules and mechanisms, but also contribute to shaping these, we make a broader theoretical point. We argue that the ‘business-as-usual’ trajectory that characterizes the irrigation sector is also rooted in the very concept of governance, which is fundamentally about “governing”, that is a practice aiming at steering people towards defined ends, and through different means such as infrastructure, management practices and policies.